Abuse-resistant lithium-ion battery cathode mixture with symbiotic power performance advantages

KR103011892B1Active Publication Date: 2026-09-01A123 SYSTEMS LLC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
KR1020217024760
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-01-07
Filing Date
2020-01-03
Publication Date
2026-09-01
Estimated Expiration
2040-01-03

Smart Images

  • Figure R1020217024760_ABST
    Figure R1020217024760_ABST
Patent Text Reader

Abstract

A method and system for a mixture of cathode active materials are provided. In one example, the mixture of cathode active materials provides a high-power battery having low DC resistance while improving the safety performance of a lithium-ion battery. A mixture of cathode active materials and a method and system for manufacturing a battery comprising said mixture are further provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] Cross-reference regarding related applications

[0002] This application claims priority to U.S. Provisional Application No. 62 / 789,399, filed January 7, 2019, titled “Abuse-Resistant Lithium-Ion Battery Cathode Mixture with Symbiotic Power Performance Advantages.” The full contents of the application listed above are incorporated herein by reference for all purposes.

[0003] Technology field

[0004] The present disclosure relates to materials and methods generally used in secondary lithium-ion batteries. Background Technology

[0005] Consumer demand for electric vehicles has been increasing in recent years. This interest in electric vehicles has been motivated by rising petroleum fuel prices, the convenience of not having to visit gas stations frequently, and the desire to reduce vehicle carbon dioxide emissions. To meet this growing demand, automakers are adopting various new technological approaches to vehicle propulsion systems. Currently, there are several sub-classes of electric vehicles (EVs) that differ in the level of hybridization between the existing internal combustion engine (ICE) and the electric motor. These sub-classes include battery electric vehicles (BEVs), plug-in hybrid electric vehicles (PHEVs), and mild hybrid electric vehicles (MHEVs).

[0006] One of the features of an MHEV is the inclusion of a 48-volt battery pack composed of 12 to 14 lithium-ion power cells connected in series. These modules must be able to receive and deliver charge pulses at very high speeds, sometimes approaching 40C. To utilize this capability, lithium-ion active materials, conductive additives, and cell designs biased for high-speed operation are required. This capability is further linked to the requirement for low direct current resistance (DCR) to prevent excessive self-heating, which may necessitate expensive auxiliary thermal management systems.

[0007] Since the pulse time for fast charge acceptance and delivery lasts up to 60 seconds, the MHEV battery state-of-charge (SOC) can fluctuate from one extreme to the other in a short period. Therefore, monitoring and controlling the SOC using an on-board battery management system (BMS) is essential for maintaining rated battery performance. Typically, a BMS calculates the SOC of individual cells based on cell voltage. This calculation is most accurate when the relationship between voltage and SOC is sloped and linear, which is LiNi x Co y Mn z This is one of the defining characteristics of a lithium-ion battery containing a positive electrode using O2 (NCM or NMC) active material. For MHEV applications, the usable SOC range of a 48-volt battery pack is typically 20-80%.

[0008] NCM active materials have undergone large-scale adoption in lithium-ion battery design due to a favorable combination of excellent theoretical energy density, compatibility with existing lithium-ion electrolytes, a sloped and smooth voltage profile, and relatively low manufacturing costs at scale. However, compared to oxide-free olivine-structured active materials such as lithium iron phosphate (LFP), NCM active materials have an inherent tendency to release oxygen under abuse conditions, such as nail penetration, hot box testing, and overcharging. When combined with flammable organic liquids that constitute the electrolyte, batteries using these active materials are susceptible to catastrophic failure modes. Mitigating these risks is an active area of ​​research and development, and these efforts have led to the emergence of many technologies implemented at both the material and battery levels. For example, one approach of the prior art described in US 9,178,215, US 9,793,538, US 2014 / 0322605, US 2017 / 0352876, and US 2014 / 0138591 was to physically mix NCM active material particles with other materials such as olivine-structured LFP or lithium iron manganese phosphate (LFMP or LMFP), which have adverse oxygen release under abuse conditions.

[0009] However, the inventors recognized potential problems associated with physically mixing NCM active material particles with other materials such as LFP and LFMP. As an example, design considerations for lithium-ion batteries requiring low DCR over a wide SOC range imply that voltage drop is minimized under high current loads. Interpreted at the material level, this requirement implies that metal-centered oxidation-reduction or redox reaction(s) involving lithium-ion insertion at the cathode must occur with a small overpotential. In the case of a mixed cathode where the mixed components are LFMP and NCM, the overpotential during a current pulse can induce a voltage swing that may traverse the voltage gap between the following thermodynamic half-cell reduction potentials:

[0010] · Transition metal center redox reaction in NCM and Fe center redox reaction in LFMP;

[0011] · Transition metal center redox reactions in NCM and Mn center redox reactions in LFMP; and

[0012] · Conversion between Fe-centered and Mn-centered redox reactions in LFMP.

[0013] In the above scenario, an SOC swing requiring a voltage swing that includes any of the described transient voltage ranges is often accompanied by a significant increase in DCR.

[0014] The voltage at which each cathode half reaction occurs is unique and cannot be modified. However, contrary to conventional knowledge, the inventors have discovered that the SOC at which such an increase in DCR occurs can be controlled by carefully manipulating the ratio of the active materials combined with the ability to adjust the composition of the active materials. In this way, a synergistic blended cathode system can be developed in which the DCR is maintained relatively constant within the target SOC range for MHEV applications.

[0015] Klein et al.'s LFMP and spinel structure LiMn at 4.0 V versus lithium for reduced electrode polarization attributed to buffering and synergistic rate capability effects between the two materials 1.9 Al 0.1 There is recent academic literature describing a similar effect between O4s. The proposed mechanism for this effect involves electron transfer between the two active substances (Klein, A.; Axmann, P.; Wohlfahrt-Mehrens, M. "LiFe 0.3 Mn 0.7 PO4-LiMn 0.9 Al 0.1 Synergistic effect of O4 mixed electrode", J. Power Sources 2016, vol. 309, pp. 169-177, and Klein, A.; Axmann, P.; Wohlfahrt-Mehrens, M. “LiFe 0.3 Mn 0.7 Origin of the synergistic effect of spinel mixtures via PO4-dynamic in-situ X-ray diffraction measurements", J. Electrochem. Soc . 2016, vol. 163, pp. A1936-A1940).

[0016] 10% LiMn 0.6 Fe 0.4 PO4 and 90% LiNi 0.33 Co 0.33 Mn 0.33Improved cycle life and capacity at 2C discharge rates using a mixture of O2 (NCM111) were reported in the scientific literature by Tian et al. (Wang, Q.; Tian, ​​N.; Xu, K.; Han, L.; Zhang, J.; Zhang, W.; Guo, S.; You, C. "LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 An easy method to improve the high-speed circulation performance of O2 cathode materials J. Alloy Compd. 2016, vol. 686, pp. 267-272). The buffering effect was quantified by Huebner et al. by short-circuiting lithium cobalt oxide (LCO) and LFP electrodes together (Heubner, C.; Liebmann, T.; L mmel, C.; Schneider, M.; Michaelis, A. "Insights into Buffer Effects Observed in Mixed Lithium Insertion Electrodes", J. Power Sources 2017, vol. 363, pp. 311-316). means of solving the problem

[0017] The inventors have identified the above problems and determined a solution to solve them at least partially. As described in detail herein, a cathode configuration and a lithium-ion battery comprising said cathode configuration are presented to overcome the difficulties presented above. In one example, the mixed cathode active material comprises a mixture of LFMP and NCM, wherein LFMP is less than NCM by weight. In additional or alternative examples, the lithium-ion battery comprises a cathode and an anode communicating through an electrolyte, and the cathode comprises LFMP and NCM, wherein NCM is more abundant than LFMP and LFMP contains 65% Mn. The mixture of LFMP and NCM provides the lithium-ion battery with the complementary advantages of high power and low DCR. The inventors have also discovered that a lithium-ion battery comprising a mixed active material cathode as described herein provides improved abuse tolerance characteristics. For example, the mixed active material cathode shows improved performance when subjected to nail penetration abuse tests, even in large (8Ah) batteries using a graphite anode and a carbonate-based electrolyte.

[0018] As an additional example, the method comprises the steps of mixing LFMP with a solvent to obtain a mixture, adding conductive carbon to the mixture, adding a binder to the mixture, adding NCM to the mixture, casting the mixture onto a current collector, evaporating the solvent from the mixture to obtain a dry active material mixture, and calendering the dry active material mixture. Thus, a cathode comprising the dry active material mixture can be incorporated into a lithium-ion battery, wherein the lithium-ion battery is thereby endowed with the advantages described above.

[0019] It will be understood that the summary above is provided to introduce, in a simplified form, a selection of concepts further described in the detailed description. This is not intended to identify the core or essential features of the claimed subject matter, the scope of which is uniquely defined by the claims following the detailed description. Furthermore, the claimed subject matter is not limited to any part of this disclosure or to any implementation addressing any of the disadvantages mentioned above. Brief explanation of the drawing

[0020] FIG. 1 is a schematic diagram of an exemplary method for manufacturing a lithium-ion battery comprising a mixed active material cathode according to at least one embodiment of the present disclosure. Figure 2 shows a graph representing the charge and discharge DCR versus SOC measured by hybrid pulse power characterization at 23 °C. Figure 3 shows a graph representing the discharge DC resistance (DCR) versus the state of charge (SOC) for a battery having a mixed cathode material. Figure 4 is a flowchart for manufacturing an electrode with a mixed cathode material. Specific details for implementing the invention

[0021] The present disclosure relates to materials and methods for mixing cathode active materials, such as a mixture of lithium iron manganese phosphate (LFMP) and lithium nickel cobalt manganese oxide (NCM), or a mixture of other lithium phosphate and / or high-nickel oxides. The mixed cathode active material may be used in the cathode of a lithium-ion battery, including the cathode of such battery found in high-power batteries and mild hybrid electric vehicles (MHEVs). The cathode active material may be in powder form and may contain secondary particles, or the material may be in the form of an electrode, as illustrated in the schematic diagram of one embodiment of the lithium-ion battery manufacturing of FIG. 1. The mixed cathode active material may be formed by wet mixing the components with a solvent, conductive carbon, and a binder, as described in the exemplary method of FIG. 4.

[0022] The inventors discovered that some LFMP-NCM mixed active materials provide increased abuse tolerance compared to conventional unmixed high-nickel oxide active materials while still maintaining the gentle slope voltage plateau characteristics of the unmixed high-nickel oxide active materials. These mixed active materials were also demonstrated to provide lower direct current resistance (DCR) between 20% and 80% state-of-charge (SOC) compared to conventional unmixed LFMP materials. For example, Fig. 2 shows the results of test runs for battery cells containing unmixed LFMP and NCM as well as mixed LFMP and NCM. Fig. 3 further shows the test results for the discharge of battery cells containing various mixed cathode active materials. As illustrated in Figs. 2 and 3, battery cells containing mixed cathode active materials exhibit synergistic power performance, in which the mixed material performs similarly to unmixed NCM in terms of DCR. In addition, the low weight ratio of high manganese LMFP is observed to function as an effective additive for maintaining the performance of mixed cathode active materials compared to other mixed cathode active materials and non-mixed counterparts.

[0023] For clarity and continuity, it should be understood that multiple names may be used to refer to the same concept, idea, or item in the following description, and vice versa. For example, "high-nickel active cathode material" refers to LiNi 0.33 Co 0.33 Mn 0.33 O2(NCM111), LiMn x' Ni 2-x' O4, LiNiPO4, LiCoPO4, or lithium nickel manganese oxide (layered or spinel structure), or Ni x' Mn y' Co 1-x'-y'(OH)2 and NiCo y' Al 1-x'-y' It should be understood that the term may be used herein to refer to any electrochemically active cathode powder used in lithium-ion batteries, including but not limited to any precursor of the above-mentioned material, such as (OH)2. Additionally, the term "high-nickel cathode" may be used to refer to any cathode composed of, containing, and / or using the aforementioned high-nickel active cathode material for lithium-ion transport between the cathode and the electrolyte of a battery cell. Thus, a cathode referred to as an "NCM cathode" is, for example, a cathode containing NCM as an electrochemically active cathode material.

[0024] In addition, numerous specific details are described to provide a thorough understanding of the concepts presented in the following description. The presented concepts may be practiced with or without some or all of these specific details. In other cases, well-known process behaviors have not been described in detail so as not to unnecessarily obscure the described concepts. While some concepts will be described in relation to specific embodiments, it will be understood that these embodiments are not intended to be limiting.

[0025] The terms used in this document are not intended to be limited to those used merely to describe specific embodiments. In this document, the singular forms (“a,” “an,” and “the”) are intended to include the plural forms containing “at least one” unless otherwise specified in the text. “Or” means “and / or.” As used herein, the term “and / or” includes any combination of one or more of the related listed items. It will be further understood that when the terms “comprises” and / or “comprising,” or “includes” and / or “including” are used herein, they specify the presence of the stated functions, areas, integers, steps, operations, elements, and / or components, but do not exclude the presence or addition of one or more other features, areas, integers, steps, operations, elements, components, and / or groups thereof. The terms “or combinations thereof” or “mixtures of” mean a combination containing at least one of the aforementioned elements.

[0026] Unless otherwise defined, all terms used herein (including technical and scientific terms) have the same meaning as generally understood by those skilled in the art to which the present invention pertains. Terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with that meaning in the context of the relevant technology and the present invention, and should not be interpreted in an idealized or overly formal sense unless explicitly defined herein.

[0027] As used herein, “excess lithium” or “lithium-rich” or “excess phosphate” or “phosphate-rich” refers to an amount of lithium or phosphate in the total composition that exceeds the amount required to form stoichiometric olivine or layered compounds.

[0028] In this specification, "specific capacity" refers to the capacity per unit mass of the electroactive material of the anode, and the unit is milliampere-hour / gram (mAh / g).

[0029] As used herein, the term “dopant” may include an element, ion, polyatomic ion, and / or chemical moiety apart from the defining composition of a given material. Additionally, a dopant may enhance the electrochemical, physicochemical, and / or safety properties of a given material. In one example, a dopant added to an LFMP may include any element, ion, polyatomic ion, or chemical moiety other than Li, Fe, Mn, or PO4. In another example, a dopant added to an NCM may include any element, ion, polyatomic ion, or chemical moiety other than Li, Ni, Co, Mn, or O2.

[0030] Referring to FIG. 1, the schematic diagram (100) illustrates an exemplary process for manufacturing a lithium-ion battery using an LFMP-NCM mixed active cathode material in the form of a slurry or a cathode.

[0031] Component A (102) of the mixed active cathode material may be LFMP (102). LFMP (102) is Li a Fe 1-x-y Mn x D y (PO4) z F wIt is a cathode active material having the overall composition of , where 1.0 ≤ a ≤ 1.10, 0.45 < x ≤ 0.85, 0 ≤ y ≤ 0.1, 1.0 < z ≤ 1.1, 0 ≤ w < 0.1, and D may be one or more dopant metals selected from the group consisting of Ni, V, Co, Nb and combinations thereof. Component A (102) may be in the form of a powder containing particles. Component A (102) may have an olivine structure.

[0032] In some embodiments, 1.0 ≤ a ≤ 1.05, 1.0 < a ≤ 1.05, 1 < a < 1.05, 1.0 < a ≤ 1.10, or 1 < a < 1.10. In some embodiments, 0.50 ≤ x ≤ 0.85, 0.50 ≤ x ≤ 0.80, 0.55 ≤ x ≤ 0.80, 0.55 ≤ x ≤ 0.75, 0.60 ≤ x ≤ 0.75, 0.60 ≤ x ≤ 0.70, 0.60 < x < 0.70, 0.65 ≤ x < 0.70, or x = 0.65. In one example, 0.60 ≤ x ≤ 0.85. In additional examples, 0.65 ≤ x ≤ 0.85. In some embodiments, 1.0 < z ≤ 1.05 or 1.0 < z ≤ 1.025.

[0033] In some embodiments, the total composition of the LMFP (102) may contain at least 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, 65 wt%, 70 wt%, 75 wt%, or 80 wt% of Mn. In one example, the total composition of the LMFP (102) may contain at least 60 wt% of Mn. In additional examples, the total composition of the LMFP (102) may contain at least 65 wt% of Mn.

[0034] In some embodiments, the total composition of the LMFP (102) may include up to about 0.1 mol%, 0.5 mol%, 1 mol%, 1.5 mol%, 2 mol%, 2.5 mol%, 3 mol%, 3.5 mol%, 4 mol%, 4.5 mol%, 5 mol%, 6 mol%, 7 mol%, 8 mol%, 9 mol%, or 10 mol% of a dopant. In certain embodiments, the total composition of the LMFP (102) may include up to 0.1 mol%, 0.5 mol%, 1 mol%, 1.5 mol%, 2 mol%, 2.5 mol%, 3 mol%, 3.5 mol%, 4 mol%, 4.5 mol%, 5 mol%, 6 mol%, 7 mol%, 8 mol%, 9 mol%, or 10 mol% of Ni. In certain embodiments, the total composition of the LMFP (102) may include up to 0.1 mol%, 0.5 mol%, 1 mol%, 1.5 mol%, 2 mol%, 2.5 mol%, 3 mol%, 3.5 mol%, 4 mol%, 4.5 mol%, 5 mol%, 6 mol%, 7 mol%, 8 mol%, 9 mol%, or 10 mol% of V. In certain embodiments, the total composition of the LMFP (102) may include up to 0.1 mol%, 0.5 mol%, 1 mol%, 1.5 mol%, 2 mol%, 2.5 mol%, 3 mol%, 3.5 mol%, 4 mol%, 4.5 mol%, 5 mol%, 6 mol%, 7 mol%, 8 mol%, 9 mol%, or 10 mol% of Co. In certain embodiments, the total composition of the LMFP (102) may contain up to 0.1 mol%, 0.5 mol%, 1 mol%, 1.5 mol%, 2 mol%, 2.5 mol%, 3 mol%, 3.5 mol%, 4 mol%, 4.5 mol%, 5 mol%, 6 mol%, 7 mol%, 8 mol%, 9 mol%, or 10 mol% of Nb. In certain embodiments, the total composition of the LMFP (102) may contain up to 0.It may contain 1 mol%, 0.5 mol%, 1 mol%, 1.5 mol%, 2 mol%, 2.5 mol%, 3 mol%, 3.5 mol%, 4 mol%, 4.5 mol%, 5 mol%, 6 mol%, 7 mol%, 8 mol%, 9 mol%, or 10 mol% of F.

[0035] Doping with hypervalent transition metals such as Nb or V can contribute to the benefits of olivine materials for rechargeable lithium-ion battery applications. The beneficial role of one or more dopants can be multiplied and may include increased electronic conductivity of the olivine material and limiting the sintering of olivine material particles, which allows for the substantial full utilization of lithium capacity during rapid charging / discharging of a given lithium-ion battery.

[0036] Excess lithium and excess phosphate in the overall composition do not need to provide a single olivine structure or a non-stoichiometric olivine compound on a single olivine. Rather, excess lithium and / or phosphate may exist as a secondary phase, for example, together with olivine. Typically, dopants such as Ni, V, Co, Nb, and / or F dope and reside in the lattice sites of the olivine structure to form an olivine phase. However, a small amount of a dopant-rich secondary phase may be allowed before the lithium-ion battery performance is significantly degraded.

[0037] In some embodiments, the LFMP (102) may be in the form of a particle such as a secondary particle. The particle may have a D50 size range greater than 0 and up to 5 μm. In some embodiments, the particle may have a D50 size range from 800 nm to 5 μm. In some embodiments, additionally or alternatively, the particle may have a D50 size range of 800 nm to 4 μm, 800 nm to 3 μm, 800 nm to 2 μm, 800 nm to 1 μm, 1 μm to 5 μm, 2 μm to 5 μm, 3 μm to 5 μm, or 4 μm to 5 μm. In some embodiments, the particle may be a secondary particle formed from a primary particle having a size range greater than 0 and up to 100 nm. In some embodiments, the D50 size range of secondary particles can be adjusted during or prior to mixing in the formation of the mixed active material slurry (112) using milling, such as milling (103). For example, in some embodiments, to adjust the D50 size range of secondary particles, the particles can be reduced through atrition by a wet milling process.

[0038] In some embodiments, during the preparation of the mixed active material cathode (116), the LFMP (102) may be mixed with a solvent (104) to obtain a mixture. The solvent (104) N It may be methyl-2-pyrrolidone (NMP). Other solvents may be used as known to those skilled in the art.

[0039] In some embodiments, during the preparation of the mixed active material cathode (116), conductive carbon (106) may be added to a mixture of LFMP (102) and solvent (104). The conductive carbon (106) may constitute up to 15% of the physical solid in the mixture. In some embodiments, the conductive carbon (106) may be 10% or less, or 5% or less of the physical solid in the mixture. In some embodiments, the conductive carbon (106) may be 15%, 1-10%, 1-8%, 1-6%, 3-10%, 3-8%, 5-15%, 5-10%, or 5-8% of the physical solid in the mixture. In one example, the conductive carbon (106) comprises 5% of the physical solid in the mixture. In some embodiments, the conductive carbon (106) may comprise one or more conductive additives. The form or composition of the conductive carbon (106) used is not particularly limited and may be known to those skilled in the art. For example, the conductive carbon (106) source may include polyvinyl alcohol, polyvinyl butyral, sugar, or other sources, or a combination of sources.

[0040] In some embodiments, a polymeric binder (108) may be added to a mixture of LFMP (102), a solvent (104), and conductive carbon (106). In one embodiment, the binder (108) may be polyvinylidene fluoride (PVDF). Other binders may be used as known to those skilled in the art.

[0041] Component B (110) or NCM (110) can be added to a mixture of LFMP (102), solvent (104), conductive carbon (106), and binder (108) to form a mixed active material slurry (112). NCM (110) is Li a' Ni x' Co y' Mn 1-x'-y' (O2) bIt may have a general formula. The formula for NCM (110) may be lithium-rich such that a' > 1, or the formula may be stoichiometric such that a' = 1. In one example, 1.0 ≤ a' ≤ 1.10. NCM (110) may be NCM111 such that x' = 1 / 3 and y' = 1 / 3, or x' = 0.33 and y' = 0.33. NCM (110) may be oxygen-rich such that b > 1, or NCM (110) may be stoichiometric such that b = 1. In one example, 1.0 ≤ b ≤ 1.10. In one example, NCM (110) is Li a' Ni x' Co y' Mn 1-x'-y' (O2) b The overall composition may have, where 1.0 ≤ a′ ≤ 1.10, x′ > 0, y′ > 0, x′ + y′ < 1.0, and 1.0 ≤ b ≤ 1.10. Component B (110) may have a layered structure. In one or more examples, component B (110) is NCM, NCA, spinel, or layered LiMn x' Ni 2-x' O4, or other high-nickel cathode materials and / or Ni x' Mn y' Co 1-x'-y' It may include one or more of any precursors of the above-mentioned substances, such as (OH)2.

[0042] NCM (110) may be in the form of a particle such as a secondary particle. The particle may have a D50 size range of 1 to 10 μm or a D50 size of about 5 μm. The D50 size range of the NCM (110) particle may overlap with the size range of the LFMP (102) particle, or one may be larger than the other. In some embodiments, the D50 size of the LFMP (102) particle may be 800 nm and the D50 size of the NCM (110) particle may be 5 μm. In some embodiments, the respective D50 sizes of the LFMP (102) particle and the NCM (110) particle may be about 5 μm. In some embodiments, the D50 size of the NCM (110) particle may be about 5 μm and the D50 size of the LFMP (102) particle may be 800 nm to 5 μm. In one example, NCM (110) may be a secondary particle comprising an agglomeration of chemically bonded, nanometer-sized primary particles.

[0043] The mixed cathode active material may contain more component B (110) than component A (102). In other words, the mixed cathode active material may contain less component A (102) than component B (110). In some examples, the mixed cathode active material may contain more NCM (110) than LFMP (102) by weight. In some examples, the mixed cathode active material may contain less LFMP (102) than NCM (110) by weight.

[0044] The mixed active material slurry (112) may be a mixture comprising component A (102), a solvent (104), conductive carbon (106), a binder (108), and component B (110). The mixed active material slurry (112) may have a mixing ratio of component A (102) to component B (110), wherein 0 < component A (102) ≤ 40% and 60% ≤ component B < 100%. In some embodiments, the component A:component B ratio may be about 1:99, 5:95, 10:90, 15:85, 20:80, 25:75, 30:70, 35:65, or 40:60. In one example, the component A:component B ratio may be up to 40:60.

[0045] In some embodiments of manufacturing a lithium-ion battery, such as a mixed active material cathode (116) or a third lithium-ion battery (130) having a mixed active material cathode (116), a mixed active material slurry (112) may be deposited or cast onto a conductive substrate (114) (also referred to as a "current collector") to form the mixed active material slurry on the conductive substrate. The current collector may be a metal foil, such as aluminum foil. The mixed active material slurry (112) may be cast to a predetermined thickness and may be cast using a slot-die coater, a doctor-blade method, or other methods known in the art.

[0046] In some embodiments, after the mixed active material slurry (112) is deposited on the current collector, the solvent (104) may be dried or evaporated by gentle heating. The resulting dried film may then be calendered to a predetermined density. After the evaporation of the solvent (104) and calendering, a mixed active material cathode (116) may be formed. Accordingly, the steps of manufacturing the mixed active material cathode (116) include mixing component A (102) and component B (110) into a mixed active material slurry (112), coating the slurry (112) onto a conductive substrate, drying the mixed active material slurry on the conductive substrate (114), compressing the coating, and calendering.

[0047] In some embodiments, there may be little to no chemical bonding or hard bonding between the particles of component A (102) and the particles of component B (110). In some embodiments, there may be ionic bonding or other mechanical bonding so that the respective particles of component A (102) and component B (110) are softly bonded. In some embodiments, the respective particles of component A (102) and component B (110) exist as a physical mixture in which there is no chemical bonding between the particles of component A (102) and the particles of component B (110).

[0048] A mixed active material cathode (116) may be suitable for assembly into a first lithium-ion battery (126). A process for forming the first lithium-ion battery (126) may include pairing the cathode (116) with an anode (120) and a separator (118) sandwiched between the cathode (116) and the anode (120). The anode (120) may be one or more of lithium metal, graphite, lithium titanate (LTO), silicon, or other materials known in the art. The separator (118) may serve to separate the anode (120) and the cathode (116) to avoid physical contact. In preferred embodiments, the separator (118) has high porosity, excellent stability with respect to an electrolyte solution, and excellent liquid-holding properties. An exemplary material of the separator (118) may be selected from a nonwoven fabric, a porous film made of a polyolefin such as polyethylene or polypropylene, or a ceramic-coated material.

[0049] The mixed active material cathode (116), separator (118), and anode (120) can be placed in a hermetically-sealed battery housing (122), such as a pouch.

[0050] Subsequently, the first lithium-ion battery (126) can be filled with an electrolyte (124) to produce a filled second lithium-ion battery (128). The electrolyte (124) can support the movement of ions and may come into further contact with the components of the second lithium-ion battery (128). The electrolyte (124) may include a lithium salt, an organic solvent such as an organic carbonate solvent, and / or an additive. The electrolyte (124) may be present throughout the second lithium-ion battery (128) and may come into further physical contact with the anode (120), cathode (116), and separator (118).

[0051] The second lithium-ion battery (128) may undergo cell formation, also known as a first charge / discharge cycle, to form the third lithium-ion battery (130). The third lithium-ion battery (130) may be a fully manufactured and complete battery cell that is ready for insertion into a lithium-ion battery (132) together with other similarly manufactured lithium-ion batteries. The third lithium-ion battery (130) may store energy as a chemical potential in component electrodes (e.g., a cathode (116) and an anode (120)), wherein the electrodes may be configured to reversibly convert between chemical energy and electrical energy through a redox reaction.

[0052] In this manner, a lithium-ion battery (132) can be manufactured, wherein a mixture of cathode active materials can be used to manufacture at least one mixed active material cathode (116) of the component battery cells of the lithium-ion battery (132). In particular, the lithium-ion battery (132) may include one or more battery cells, wherein each battery cell may be a third lithium-ion battery (130). One or more battery cells may include a cathode (116) containing a mixed cathode active material, a separator (118), an electrolyte (124), and an anode (120). The mixed active material cathode (116) can be manufactured by mixing component A (102), a solvent (104), conductive carbon (106), a binder (108), and component B (110) to form a mixed active material slurry (112), and subsequently applying it to a current collector, drying, and calendering.

[0053] In one example, the lithium-ion battery (132) may include a cathode (116) and a complementary anode (120), wherein the lithium-ion battery (132) may be additionally arranged in a device, wherein the device may be an electric vehicle, a hybrid electric vehicle, a mobile phone, a smartphone, a satellite positioning system device, a tablet device, or a computer.

[0054] In some embodiments, the process for forming the mixed active material cathode (116) may differ from that described above. In some embodiments, component A (102) and component B (110) may be dry-mixed to form a dry active material mixture. In some embodiments, the mixed active material slurry (112) may be dried before being applied to a current collector to achieve a dry active material mixed powder. In some embodiments, additional additives or processes may be included, or alternatively, additives or processes may be removed or substantially altered.

[0055] Figures 2 and 3 show the test results for the charge / discharge DCR of battery cells using mixed cathode active materials. In lithium-ion batteries where LFMP acts as the anode, two lithium de-insertion plateaus occur in the voltage versus charge capacity graph: one centered at 3.5 V versus lithium and the other centered at 4.1 V versus lithium. The 3.5 V plateau largely corresponds to the following redox reaction:

[0056] LiFe 2+ Mn 2+ D y (PO4) z → n Li + + n e - + Li 1- n Fe 3+ Mn 2+ D y (PO4) z

[0057] The 4.1V ballast primarily corresponds to the following redox reactions:

[0058] Li 1- n Fe 3+ Mn 2+ D y (PO4) z → m Li + + m e - + Li 1- n - m Fe 3+ Mn 3+ D y (PO4) z

[0059] Similarly, during discharge or lithium-ion insertion, two stabilizers occur in the voltage versus discharge capacity graph: one centered at 4.0 V versus lithium and the other at 3.45 V versus lithium. These reactions largely correspond to the reverse reactions described above and are centered on Mn and Fe atoms, respectively.

[0060] To obtain a low DCR (and thus high power) with a lithium-ion battery using an NCM active material, it may be necessary to maximize the ionic and electronic conductivity of the active material, respectively, at the particle level. Practically speaking, ionic conductivity is inversely proportional to particle size and porosity. The NCM active material used herein may have a D50 particle size of approximately 5 μm. In some embodiments, the D50 particle size of the NCM active material may be in the range of 1–10 μm. The NCM active material is 0.5 m 2 It can have a BET (Brunauer-Emmett-Teller) surface area greater than / g. In some embodiments, the BET surface area of ​​the NCM active material is > 1 m 2 It can be / g.

[0061] Electronic conductivity can be tuned based on the inclusion of dopants, conductive coatings, and tuning bulk compositions. Generally, the electronic conductivity trend for NCM active materials can be directly proportional to the proportion of cobalt in a given particle, which means, for example, that NCM111 is more electrically conductive than NCM622. In lithium-ion batteries where NCM111 acts as the anode, a smooth and gently sloping onset of the stabilizer is observed at 3.75 V to lithium during the charging phase. This lithium deintercalation stabilizer corresponds to a mixture of nickel- and cobalt-centered redox reactions. The degree of lithium deintercalation is controlled by an upper cutoff voltage. This voltage is generally limited to 4.4 V to lithium or lower to mitigate adverse side reactions associated with irreversible phase transitions on the particle surface and electrolyte oxidation.

[0062] Based on experimental results, the inventors identified several factors related to obtaining a low DCR with a cathode composed of a physical mixture of LFMP (component A) (102) and NCM (component B) (110).

[0063] Mixing ratio of component A (102) to component B (110). From the perspective of cost and abuse tolerance, it may be advantageous to maximize the contribution of component A (102). Capacity density (mAh / g and mAh / cm²) 3 From the perspective of ), it may be advantageous to maximize the contribution of component B (110). To reach a target mixing ratio, the balance of these factors must be considered. The inventors of the present invention have found that an active substance ratio of 0 < component A ≤ 0.4 and, conversely, 0.6 ≤ component B < 1.0 can benefit from the beneficial qualities of each component A (102) and component B (110) and thus be commercially attractive.

[0064] Voltage superposition between component A (102) and component B (110).The DCR advantage of the mixed active material cathode (116) can exist only when the working voltages of component A (102) and component B (110), respectively, are compatible. Consequently, the mixed active material cathode (116) may be disadvantageous when voltage compatibility is poor. To keep the voltage profile as smooth as possible, the ratio between component A (102) and component B (110) may also need to be considered. Generally, as the ratio of component A (102) changes relative to component B (110), the composition of component A (102) must also change to maintain the advantage of the lithium-ion battery containing the mixed active material cathode (116). Specifically, the ratio of Mn and Fe may be selected to maximize voltage overlap. For a mixed active material cathode (116), one exemplary mixture capable of providing excellent voltage overlap (and thus excellent DCR over a wide SOC range) is Li mixed with NCM111 in a ratio of 0.3:0.7. 1.05 Fe 0.34 Mn 0.63 D 0.03 It is (PO4).

[0065] Specific capacity overlap between component A (102) and component B (110). The reversible charge capacity over the operating voltage range can be similar on a mass basis. This avoids a significant increase in mass loading for a given electrode area, which could reduce the electrochemical performance and abuse resistance gains that the mixture can provide (vs. single-component cathode).

[0066] The power (and DCR) performance of the mixed cathode can be evaluated by a hybrid pulse power characterization (HPPC) test. The HPPC test measures voltage drop under high-current discharge and charge conditions incrementally across the entire SOC range. Figure 2 shows the charge (graph (202)) and discharge (graph (252)) DCR versus SOC of mixed and non-mixed cathodes measured by the HPPC test at 23 °C. Curve (204) shows the DCR versus SOC at a 3.5C charge of an LFMP containing 65% Mn. Curve (204) shows a significant increase in DCR at approximately 30% SOC. Curve (206) shows the DCR versus SOC at a 3.5C charge of an NCM111. Curve (206) shows a consistently lower DCR than Curve (204) as well as the absence of significant DCR spikes. Curve (208) shows the DCR versus SOC in a 3.5C charge of a mixed material containing 20% ​​LFMP (65% Mn) and 80% NCM111. Curve (208) shows that the DCR of the mixed material between 20% and 80% SOC is closely related to the DCR of pure NCM111 (curve (206)). In particular, as can be seen in LFMP (curve 204), there is no DCR peak at 30% SOC. The DCR of curve (208), which matches the DCR of curve (206) very closely, suggests a synergistic relationship between LFMP and NCM111 in the mixed material. That is, despite the fact that 20% of the mixture (e.g., LFMP) has a higher DCR when tested on its own, as evidenced by curve (204), the DCR of the mixture remains relatively flat and is not greater than the DCR of pure NCM111 (curve (206)).

[0067] Graph (252) shows a similar synergistic effect on DCR occurring even during discharge. Curve (254) shows DCR versus SOC during 5C discharge of LFMP containing 65% Mn. Curve (254) shows a significant increase in DCR at approximately 30% SOC. Curve (256) shows DCR versus SOC during 5C discharge of NCM111. Curve (256) shows a lack of significant DCR spikes as well as consistently lower DCR than Curve (254). Curve (258) shows DCR versus SOC during 5C discharge of the mixed material. Curve 258 shows that between 20% and 80% SOC, the DCR of the mixed material is closely related to the DCR of pure NCM111 (Curve (256)). In particular, as can be seen in LFMP (Curve (254)), there is no DCR peak at 30% SOC. The DCR of curve (258), which matches very closely with the DCR of curve (256), again suggests a synergistic relationship between LFMP and NCM111 in the mixture. That is, despite the fact that 20% of the mixture (e.g., LFMP) has a higher DCR when tested individually, as demonstrated by curve (254), the DCR of the mixture remains relatively flat and is not greater than the DCR of pure NCM111 (curve (256)).

[0068] Now, referring to FIG. 3, graph (302) shows the discharge DCR for a plurality of whole cells, each whole cell comprising one of a plurality of mixed cathode active material compositions. The mixed cathode active material of each whole cell has a weight ratio of 80% NCM111 and 20% lithium transition metal phosphate. The lithium transition metal phosphate may be lithium iron phosphate (LFP; curve (304)), lithium manganese phosphate (LMP; curve (306)), LMFP containing 45% Mn (curve (308)), and LMFP containing 65% Mn (curve (310)). Graph (352) shows an enlarged view of the curves (308 and 310) in the lower left section of graph (302) to highlight the difference in discharge DCR trends.

[0069] As illustrated by graph (302), the entire cells containing LFP and LMP mixtures (curves (304 and 306), respectively) show higher DCR at lower SOC values ​​than the LMFP mixture (curves (308 and 310)). However, the inclusion of Mn in the lithium transition metal phosphate results in a flat and sustained discharge DCR across the SOC value range. This Mn advantage is visible in the LMP mixture (curve (306)) and the LMFP mixture (curves (308 and 310)). Additionally, the LMFP mixture containing 65% Mn in the LMFP (curve (310)) consistently exhibits a lower discharge DCR than the LMFP mixture containing 45% Mn in the LMFP (curve (308)). Graph (352) further illustrates the lower discharge DCR of curve (310) relative to curve (308) and expands the discharge DCR value in a lower subset of the range of SOC values. Thus, NCM mixed with high Mn lithium transition metal phosphate is observed to maintain performance over a wide SOC range.

[0070] Now, referring to FIG. 4, a method (400) for manufacturing a mixed active material cathode is provided. The mixed active material cathode may be a mixed active material cathode (116), wherein additional components (e.g., component A (102), component B (110), etc.) described with reference to the cathode and method (400) may be described in more detail above with reference to FIG. 1.

[0071] The method (400) begins at step (402), where component A (102) is mixed and dissolved with a solvent (104) (e.g., NMP) to obtain a mixture. For example, the weight percentage of component A (102) dissolved in the solvent (104) may be greater than 0 wt% to about 40 wt%. In another example, the weight percentage of component A (102) dissolved in the solvent (104) may be about 10 wt% to 30 wt%, or about 20 wt%. In one example, at step (402), the method (400) may include forming a dissolved LFMP solution by dissolving particles of LFMP (102) in NMP or another solvent (104).

[0072] In step (404), conductive carbon (106) may be added to the mixture. The form or composition of the conductive carbon (106) is not particularly limited and may be any type known to those skilled in the art. For example, the conductive carbon (106) may include graphite, graphene, ketjen black, carbon black, or other forms or compositions of conductive carbon (106). The conductive carbon (106) may include or be replaced by other conductive additives, including but not limited to metal powder, metal oxide, and / or conductive polymer. In one example, the conductive carbon (106) may be added in an amount between 0 wt% and about 15 wt%. For example, the mass percentage of the conductive carbon (106) may be between 0% and about 15% of all combined solids in the mixture. In another example, the conductive carbon (106) may be added in an amount between 0 wt% and about 5 wt%. In another example, conductive carbon (106) may be added in an amount of about 5 wt% to about 10 wt%. In one example, conductive carbon (106) is added in an amount of 5 wt%.

[0073] In step (406), a binder (108) may be added to the mixture. The binder (108) may be PVDF or one or more other binders known to those skilled in the art.

[0074] In step (408), component B (110) may be added to the mixture. Component B (110) may be NCM (110). NCM (110) is Li a' Ni x' Co y' Mn 1-x'-y'It may have the general chemical formula of O2. The chemical formula for NCM (110) may be lithium-rich such that a' > 1, or the chemical formula may be stoichiometric such that a' = 1. NCM (110) may be NCM (111) such that x' = 1 / 3 and y' = 1 / 3, or x' = 0.33 and y' = 0.33. Component B (110) may have a layered structure. In one example, the mass percentage of component A (102) may be greater than 0% to about 40% of the total weight of component A (102) and component B (110). In additional or alternative examples, the mass percentage of component B (110) may be about 60% to less than 100% of the total weight of component A (102) and component B (110).

[0075] NCM (110) may be in the form of a particle such as a secondary particle. The particle may have a D50 size range of 1 to 10 μm or a D50 size of about 5 μm. The D50 size range of the NCM (110) particle may overlap with the size range of the LFMP (102) particle, or one may be larger than the other. In some embodiments, the D50 size of the LFMP (102) particle may be 800 nm and the D50 size of the NCM (110) particle may be 5 μm. In some embodiments, the D50 size of each of the LFMP (102) particle and the NCM (110) particle may be about 5 μm. In some embodiments, the D50 size of the NCM (110) particle may be about 5 μm and the D50 size of the LFMP (102) particle may be 800 nm to 5 μm.

[0076] In step (410), the mixture may be cast or deposited onto a current collector (e.g., a metal foil such as aluminum foil). In step (410), a slot die coater, a doctor blade method, or other techniques may be used to cast the mixture to a predetermined thickness.

[0077] In step (412), the solvent can be evaporated from the mixture to obtain a dried mixed active material. In one example, the mixture may be heated to increase the evaporation rate.

[0078] In step (414), the dried mixed active material can be calendered to a predetermined density. Then, the method (400) is terminated.

[0079] In additional examples, a lithium-ion battery comprising a mixed cathode active material as described herein may provide improved abuse resistance characteristics. For example, the lithium-ion battery demonstrates improved performance in a nail penetration abuse test. In particular, a lithium-ion battery comprising a mixed cathode active material as described herein, comprising at least LFMP and NCM in which the respective particle distributions, operating voltages, and / or specific capacities of LFMP and NCM overlap, exhibits improved abuse resistance.

[0080] In this way, by mixing high-manganese LFMP active material and NCM active material and using them as the cathode of a lithium-ion battery, a safer and longer-lasting battery can be obtained. In particular, as a result, less oxygen is emitted under abuse conditions by the combined active material compared to NCM alone. This phenomenon of mitigating oxygen gas can prevent a decrease in the flash point of the electrolyte within the battery. Therefore, through the formulation of active materials as disclosed herein, technical effects can be obtained to enhance battery safety and reduce battery fires.

[0081] In addition, the technical effect of mitigating the relatively high DCR of LFMP is achieved herein. NCM was shown to mitigate both the relatively high DCR and the associated DCR spikes of LFMP. In this way, high-power batteries can be manufactured that provide a large and smooth voltage curve between 20% and 80% SOC. This allows the battery management system (BMS) to effectively regulate and control the battery SOC, for example in MHEVs.

[0082] A mixed cathode active material for a lithium-ion battery comprises lithium iron manganese phosphate (LFMP)—said that the LFMP contains at least 40 wt% Mn—and lithium nickel cobalt manganese oxide (NCM), wherein, on a weight basis, the LFMP is less than the NCM. In the first example of the mixed cathode active material, the LFMP additionally comprises LiaFe 1-x-y Mn x D y (PO4)F wIt has an overall composition of , where 1.0 ≤ a ≤ 1.10, 0.45 < x ≤ 0.85, 0 ≤ y ≤ 0.1, 1.0 < z ≤ 1.1, 0 ≤ w < 0.1, and D can be selected from the group consisting of Ni, V, Co, Nb, and combinations thereof. In the second example of a mixed cathode active material optionally comprising the first example of a mixed cathode active material, the LFMP is additionally lithium-rich. In the third example of a mixed cathode active material optionally comprising the first and second examples of mixed cathode active materials, 0.60 ≤ x ≤ 0.85 is additionally 0.60 ≤ x ≤ 0.85. In the fourth example of a mixed cathode active material optionally comprising the first to third examples of mixed cathode active materials, the LFMP is additionally in the form of particles having a D50 size range of 800 nm to 5 μm. In the fifth example of a mixed cathode active material optionally comprising the first to fourth examples of mixed cathode active materials, the mass percentage of the LFMP is further greater than 0% and less than about 40% of the total weight of the LFMP and the NCM. In the sixth example of a mixed cathode active material optionally comprising the first to fifth examples of mixed cathode active materials, the NCM is further Li a' Ni x' Co y' Mn 1-x'-y' (O2) bIt has an overall composition of, where 1.0 ≤ a' ≤ 1.10, x' > 0, y' > 0, x' + y' < 1.0, and 1.0 ≤ b ≤ 1.10. In the seventh example of a mixed cathode active material optionally comprising the first to sixth examples of mixed cathode active materials, x' = 0.33 and y' = 0.33. In the eighth example of a mixed cathode active material optionally comprising the first to seventh examples of mixed cathode active materials, the NCM is additionally in the form of particles having a D50 size of about 5 μm. In the ninth example of a mixed cathode active material optionally comprising the first to eighth examples of mixed cathode active materials, the NCM is additionally > 1 m 2 It has a BET (Brunauer-Emmett-Teller) surface area of ​​g / g. In the 10th example of a mixed cathode active material optionally comprising the 1st to 9th examples of mixed cathode active materials, the mass percentage of the NCM is further about 60% to less than 100% of the total weight of the LFMP and the NCM. In the 11th example of a mixed cathode active material optionally comprising the 1st to 10th examples of mixed cathode active materials, the LFMP:NCM ratio is further about 30:70. In the 12th example of a mixed cathode active material optionally comprising the 1st to 11th examples of mixed cathode active materials, the operating voltages of the LFMP and the NCM are further overlapped. In the 13th example of a mixed cathode active material optionally comprising the 1st to 12th examples of mixed cathode active materials, the specific amounts of the LFMP and NCM are further overlapped.

[0083] In another example, the method comprises the steps of: mixing a first amount of lithium iron manganese phosphate with a solvent to obtain a mixture—the lithium iron manganese phosphate contains at least 60 wt% Mn—; adding conductive carbon to the mixture; adding a binder to the mixture; adding a second amount of lithium nickel cobalt manganese oxide to the mixture—the second amount of lithium nickel cobalt manganese oxide is greater by weight than the first amount of lithium iron manganese phosphate—; casting the mixture onto a current collector; evaporating the solvent from the mixture to obtain a dried mixed active material; and calendering the dried mixed active material. In the first example of the method, the conductive carbon is additionally added in an amount between 0 wt% and about 5 wt%. In the second example of the method optionally comprising the first example of the method, the binder is additionally polyvinylidene fluoride. In a third example of a method optionally comprising one or more of the first and second examples of a method, the solvent additionally N -methyl-2-pyrrolidone( N -methyl-2-pyrrolidone)

[0084] In another example, a lithium-ion battery comprises a cathode and an anode communicating through an electrolyte, wherein the cathode comprises lithium iron manganese phosphate (LFMP) and lithium nickel cobalt manganese oxide (NCM), wherein the NCM is more abundant than the LFMP, and the LFMP comprises at least 60 wt% Mn. In the first example of a lithium-ion battery, the lithium-ion battery is arranged in a device, the device being an electric vehicle, a hybrid electric vehicle, a mobile phone, a smartphone, a satellite positioning system device, a tablet device, or a computer.

[0085] Various modifications of the invention other than those depicted and described herein will be apparent to those skilled in the art. Such modifications are also intended to fall within the scope of the appended claims. The foregoing description illustrates specific embodiments of the invention but does not imply any limitation on the practice of the invention. The foregoing discussion should be understood as illustrative and should not be construed as restrictive in any sense. Although the invention has been depicted and described with reference to particularly preferred embodiments, it will be understood by those skilled in the art that various modifications of form and detail may be made without departing from the spirit and scope of the invention as defined by the claims. The corresponding structures, materials, actions, and equivalents of all means or steps and functional elements in the claims below are intended to include any structures, materials, or actions to perform a function in combination with other specifically claimed elements.

[0086] Finally, it will be understood that the articles, systems, and methods described above are embodiments of the present disclosure—and are non-limiting examples in which numerous variations and extensions are also considered. Accordingly, the present disclosure includes all novel and non-obvious combinations and sub-combinations of the articles, systems, and methods disclosed herein, as well as any equivalents thereof.

[0087] The following claims point to specific combinations and subcombinations that are considered particularly novel and not obvious. Such claims may refer to a “one” element or a “first” element or an equivalent thereof. Such claims should be understood to include the integration of one or more such elements, without requiring or excluding two or more such elements. Other combinations and subcombinations of the disclosed features, functions, elements and / or attributes may be claimed through modifications to these claims or through the presentation of new claims in this application or related applications. Such claims may be broader or narrower in scope, the same or different from the original claims, and are also considered to be included in the subject matter of this disclosure.

Claims

Claim 1 As a blended cathode active material for a lithium ion battery, lithium iron manganese phosphate (LFMP)—the above LFMP is Li a Fe 1-x-y Mn x D y (PO4) Z F w A mixed cathode active material having an overall composition of 1.0 < a ≤ 1.10, 0.60 < x < 0.70, 0 ≤ y ≤ 0.1, 1.0 < z ≤ 1.1, 0 ≤ w < 0.1, wherein D can be selected from the group consisting of Ni, V, Co, Nb and combinations thereof; and comprising lithium nickel cobalt manganese oxide (NCM), wherein, on a weight basis, the LFMP is less than the NCM, and the LFMP is a lithium-rich material. Claim 2 delete Claim 3 delete Claim 4 A mixed cathode active material according to claim 1, wherein the LFMP is in the form of particles having a D50 size in the range of 800 nm to 5 μm and 0 ≤ y ≤ 0.

05. Claim 5 A mixed cathode active material according to claim 1, wherein the mass percentage of the LFMP is greater than 0% and less than or equal to 40% of the total weight of the LFMP and the NCM. Claim 6 In claim 1, the NCM is Li a' Ni x' Co y' Mn 1-x'-y' (O2) b A mixed cathode active material having an overall composition of 1.0 ≤ a' ≤ 1.10, x' > 0, y' > 0, x' + y' < 1.0 and 1.0 ≤ b ≤ 1.

10. Claim 7 A mixed cathode active material according to claim 1, wherein the NCM is in the form of particles having a D50 size in the range of 1 to 10 μm. Claim 8 In claim 1, the NCM is > 1 m 2 Mixed cathode active material having a BET (Brunauer-Emmett-Teller) surface area of ​​ / g. Claim 9 A mixed cathode active material according to claim 1, wherein the operating voltages of the LFMP and the NCM overlap. Claim 10 A mixed cathode active material according to claim 1, wherein the specific capacities of the LFMP and NCM overlap. Claim 11 In the method: a step of mixing a first amount of lithium iron manganese phosphate with a solvent to obtain a mixture—said that the lithium iron manganese phosphate is Li a Fe 1-x-y Mn x D y (PO4) Z F w Having an overall composition of 1.0 < a ≤ 1.10, 0.60 < x < 0.70, 0 ≤ y ≤ 0.1, 1.0 < z ≤ 1.1, 0 ≤ w < 0.1, and D can be selected from the group consisting of Ni, V, Co, Nb and combinations thereof, and the lithium iron manganese phosphate is lithium-rich; adding conductive carbon to the mixture; adding a binder to the mixture; adding a second amount of lithium nickel cobalt manganese oxide to the mixture—the second amount of lithium nickel cobalt manganese oxide has a weight greater than the first amount of lithium iron manganese phosphate—; casting the mixture onto a current collector; evaporating the solvent from the mixture to obtain a dried mixed active material; A method comprising the step of calendering the dried mixed active material. Claim 12 A method according to claim 11, wherein the conductive carbon is included in the mixture in an amount of 5% or less of the physical solid in the mixture. Claim 13 A method according to claim 11 or 12, wherein the binder is polyvinylidene fluoride. Claim 14 In Clause 11, the above solvent is N -methyl-2-pyrrolidone( N -methyl-2-pyrrolidone) method. Claim 15 A lithium-ion battery comprises a cathode and an anode communicating through an electrolyte, wherein the cathode comprises lithium iron manganese phosphate (LFMP) and lithium nickel cobalt manganese oxide (NCM), and the NCM is present in greater quantities than the LFMP; and the LFMP is Li a Fe 1-x-y Mn x D y (PO4) Z F w The LFMP has an overall composition of 1.0 < a ≤ 1.10, 0.60 < x < 0.70, 0 ≤ y ≤ 0.1, 1.0 < z ≤ 1.1, 0 ≤ w < 0.1, and D can be selected from the group consisting of Ni, V, Co, Nb and combinations thereof, and the LFMP is a lithium-rich lithium-ion battery. Claim 16 In paragraph 15, the lithium-ion battery is arranged in a device, and the device is an electric vehicle, a hybrid electric vehicle, a mobile phone, a smartphone, a satellite positioning system device, a tablet device, or a computer. Claim 17 A lithium-ion battery comprises a cathode and an anode communicating through an electrolyte, wherein the cathode comprises lithium iron manganese phosphate (LFMP) and lithium nickel cobalt manganese oxide (NCM), and the LFMP comprises Li 1.05 Fe 0.34 Mn 0.63 D 0.03 A lithium-ion battery comprising (PO4), wherein D can be selected from the group consisting of Ni, V, Co, Nb and combinations thereof, wherein the NCM is NCM111, and the LFMP is mixed with the NCM in a ratio of 0.3:0.

7. Claim 18 delete Claim 19 delete Claim 20 delete

Citation Information

Patent Citations

  • Positive electrode and lithium ion secondary battery

    JP2018037380A

  • Blended cathode materials

    KR1020140068893A